BUKTI EMPIRIS FENOMENA UNDERPRICING DAN PENGARUH MEKANISME CORPORATE GOVERNANCE - Arif Lukman Santoso, Lulus Kurniasih & (Universitas Slamet Riyadi, 2008)
Abstract This research is based on the phenomenon underlying initial public offering (IPO), underpricing. The purpose of this study is to investigate the existence of underpricing phenomena and the affect of corporate governance mechanism on underpricing. Corporate governance has three areas, which are ownership structure, board structure, and transparency. Managerial ownership and institutional ownership are used as proxy of ownership structure, board of commissioner size is used as proxy of board structure, and audit quality is used as proxy of transparency. It is hypothesized that corporate governance mechanism has influence on underpricing. Independent sample t-test and multiple regression is used to test hypothesis developed in this study. The evidence shows there is significant underpricing phenomena following IPO. Corporate governance mechanism is found not significantly influence underpricing phenomena. Keywords: IPO, underpricing, corporate governance.